พุทธปรัชญาเรื่องกรรมและการให้ผลของกรรม - ปรีชา คุณาวุฒิ (จุฬาลงกรณ์มหาวิทยาลัย, 1978)
The source of karmic theory can be traced back to the ancient concept of "Rta" in the Veda. This concept later on gradually developed and was applied into the moral realm and then generally accepted in the Upanisads. As soon as Buddhism was firmly established, it appeared that the Buddha recognized this concept in some aspect and also elaborated it in detail. In a sense, we may say that the essential core of Buddhism can be summed up by this concept or in other words by the very word "karma" both in Metaphysical and ordinary level of senses. So Buddhism may be called "Karma-Vaãda," which is diametrically opposite to "Akiriya-Vãda," the doctrine existing at that time. The Buddhist concept of karma can be derived from two sources: the one as exposed in Suttanta Texts and the other as explained in the commentary. This does not mean that both are different in their essence, but they are complement to each other instead. According to Suttanta, the karmas are of four kinds: (1) black karma having black result, (2) white karma having white result, (3) black and white karma having black and white result, and (4) neither-black-nor-white karma having neither-black-nor¬-white result. In the commentary, the commentator tries to gather the various concepts scattered in the Suttanta and put into a systematic theory, the purpose of which is to make it more coherent and comprehensible. This is the reason why we find the twelve kinds of karmas in three groups, namely (1) karma characterized by time, (2) karma characterized by force, and (3) karma charac¬terized by function. We find that the theory of karma plays the vital part also in the Buddhist ethics. This is because the moral judgement of good and evil is based on the karmic theory in toto, or in other words, a man can make a new and careful choice because of his knowledge of right and wrong karma. Again, it can be said that in some aspect, a man at present is determined by his previous actions, but his past unwholesome karma can be weakened to some extent by his new meritorious karma. Suffice it to say here that any man has the freedom to make his suitable and new way of life opposite to the past undesirable one. The Buddhist karmic theory is not a mere fantastic theory for the purpose of explaining phenomena. According to Buddhism, karma is the universal law, not related only to the time whether the past, the present or the future. This law expounds always that the doer must obtain his result inexorably and properly. The Buddhist teaching, therefore, is not the hypothesis only for the sake of moral explanation as it is said in Kant s Practical Reason, but it is the actual principle or law which says nothing but the fact that every kind of the present results grow from the soil of the past karmas and from the present they must be reaped again in future surely and inevitably. As it is seen from the above mentioned, the Buddhist karmic theory is more complete than the same theory in Brahmanism. The reason for this, is that Buddhism lays down the autonomous princi¬ple for the explanation both in the present and in the future. This law can function independently without the interference of the Absolute God, and it consoles the heart of all men better than the moral theory which is limited only to the present. This is because the Buddhist karmic theory confirms that the results of karma must be reaped whether in this life or in the next life and above all it says that a man is the architecture of his own future.